2021
DOI: 10.3390/v13112265
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley Fever Virus Propagates in Human Villous Trophoblast Cell Lines and Induces Cytokine mRNA Responses Known to Provoke Miscarriage

Abstract: The mosquito-borne Rift Valley fever (RVF) is a prioritised disease that has been listed by the World Health Organization for urgent research and development of counteraction. Rift Valley fever virus (RVFV) can cause a cytopathogenic effect in the infected cell and induce hyperimmune responses that contribute to pathogenesis. In livestock, the consequences of RVFV infection vary from mild symptoms to abortion. In humans, 1–3% of patients with RVFV infection develop severe disease, manifested as, for example, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The intertwined structure of the labyrinth zone provides the primary means of nutrient, oxygen, and waste exchange between the mother and fetus. The basal zone (also called junctional zone) is also a fetal derived tissue that helps to maintain pregnancy through production of steroids and hormones [ 23 , 24 ]. This section of placenta contains spongiotrophoblasts, trophoblast giant cells, and trophoblast glycogen cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intertwined structure of the labyrinth zone provides the primary means of nutrient, oxygen, and waste exchange between the mother and fetus. The basal zone (also called junctional zone) is also a fetal derived tissue that helps to maintain pregnancy through production of steroids and hormones [ 23 , 24 ]. This section of placenta contains spongiotrophoblasts, trophoblast giant cells, and trophoblast glycogen cells.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, ex vivo infection of second trimester [ 21 ] and full-term human placentas [ 12 ] showed infection of cytotrophoblasts and syncytiotrophoblasts of chorionic villi, which correlates with infection of similar cells in the labyrinth zone (cytotrophoblasts and syncytiotrophoblasts) and basal zone (giant cells) of rats. Immortalized human trophoblast cell lines (A3 and Jar), are also permissive to RVFV infection [ 24 ]. Despite general similarities in cellular constituents, there are distinct differences in the structure of placentas in rats and humans which should be considered when using rats as a model to study human disease.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ex vivo infection of second trimester (McMillen et al, 2018) and full-term human placentas (Oymans et al, 2020) showed infection of cytotrophoblasts and syncytiotrophoblasts of chorionic villi, which correlates with infection of similar cells in the labyrinth zone (cytotrophoblasts and syncytiotrophoblasts) and basal zone (giant cells) of rats. Immortalized human trophoblast cell lines (A3 and Jar), are also permissive to RVFV infection (Gwon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression or association with an elevated concentration of TGF-β1 in different viral infections have been thought or reported as a result of system or local immune response to protect against viral pathogens such as IAV, HIV, SARS-CoV-2, hepatitis E virus, chikungunya virus, Rift Valley Fever Virus, etc. [ 217 , 218 , 219 , 220 , 221 , 222 , 223 ]. However, its functions related to the viral infection and the viral life cycle have not always been well addressed, including the viruses of the typical ToRCH pathogens and other known potentially transplacental transmissions, or recently emerging viruses such as ZIKV and SARS-CoV-2.…”
Section: Roles Of Tgf β In Viral Infection At the Non-maternal–fetal ...mentioning
confidence: 99%